Histopathologic Changes in Disease‐Resistant‐Line and Disease‐Susceptible‐Line Juvenile Rainbow Trout Experimentally Infected with Flavobacterium psychrophilum. Issue 3 (7th August 2014) - Marancik, David P.; Leeds, Timothy D.; Wiens, Gregory D.
Abstract: A challenge to selectively breeding fish populations for improved disease resistance in aquaculture is an incomplete understanding of how artificial selection affects innate immunity at the host–pathogen level. The objective of this study was to determine whether Rainbow Trout Oncorhynchus mykiss bred for differential susceptibility to bacterial cold‐water disease exhibited altered tissue damage and cellular inflammatory response following experimental challenge with Flavobacterium psychrophilum . Fish from disease‐resistant (ARS‐Fp‐R) and disease‐susceptible (ARS‐Fp‐S) lines were experimentally challenged as juveniles, and mortalities, as well as survivors, were sampled for histopathology during the acute phase of the disease. Microscopic lesions were quantified or semiquantified and statistically compared for changes over time and between genetic lines. Significant progression in the degree of perisplenitis, splenic necrosis, splenic inflammatory infiltrates, average splenic ellipsoid area, total splenic ellipsoid area, and peritonitis was present over time in both genetic lines on at least one postinfection time point. No differences were found between renal inflammatory infiltrates and renal hematopoietic cell depletion over time. Perisplenitis was significantly lower in fish from the ARS‐Fp‐R line on day 9 postinfection than in fish from the ARS‐Fp‐S line. The ARS‐Fp‐R line demonstrated a trend towards reduced splenic necrosis compared with the ARS‐Fp‐S line that approached significance, and fish from the ARS‐Fp‐S line were 3.6 times more likely than fish from the ARS‐Fp‐R line to have a higher splenic necrosis lesion score after day 3 postinfection. These findings support the hypothesis that differential survival is a result of divergence in disease magnitude and not altered disease course between genetic lines. Characterization of histopathologic changes between genetic lines and over time helps elucidate mechanisms of disease resistance and contributes to our understanding of disease pathogenesis in fish infected with F. psychrophilum . Received January 7, 2014; accepted March 10, 2014